Randomised Control Trial Comparing Cypermethrin-Based Preparations in the Prevention of Infectious Bovine Keratoconjunctivitis in Cattle - Jennifer Allan; Steven Van Winden (Animals, 2020)
Infectious bovine keratoconjunctivitis (IBK) caused by Moraxella bovis is commonly seen in the summer months spread by face flies. This trial investigated the difference in incidence of IBK cases from natural exposure between two groups of animals, one treated with Cypermethrin pour-on preparation (PON, n = 98) and one with Cypermethrin impregnated ear tags (TAG, n = 99). Daily Live Weight Gain (DLWG) difference was investigated between animals with cases and those without and between treatment groups. A randomised positive control study, enrolled 197 animals split into two treatment groups. Cases of IBK and DLWG were recorded over the grazing season (April−November 2018). Fifty-four cases of IBK were recorded. There was no association between the two treatment groups (p = 0.362) and case status. Breed and under 12 months old were significant factors for having a case; (OR 2.3, p = 0.014 and OR 3.5, p < 0.001 respectively). There was no difference in DLWG between animals that had a case and animals that had not (p = 0.739) or between the two treatment groups (p = 0.215). Based on our results, there is no significant difference between PON or TAG preparations in the prevention of IBK. Younger animals and white-faced breeds are significantly more likely to suffer with IBK.